MULTIPLE INTELLIGENCE BASED-EDUCATION Mewujudkan Indonesia sebagai Bangsa Para Juara - Ziadatul Husnah (Al-Mudarris, 2018)
This article discusses on the urgence of multiple intelligences-based education.  In education, the multiple intelligences approach is very relevant to the spirit of education as a process of humanizing human being. Everyone should be served individually because he/she has different potential. Therefore, indicator of achievement is depended on the individual uniqueness. There is no single indicator on achievement. The multiple intelligences highlightes there are nine kinds of intelligence, namely linguistic intelligence, logical-mathematical intelligence, rythmic-musical intelligence, visual-spatial intelligence, bodily-kinesthetic intelligence, intrapersonal intelligence, interpersonal intelligence, natural intelligence, and existential intelligence. Through this approach, the educational process should be able to produce many champions suitable of each potential